Behavioral ecology of reintroduced Orangutans in the Bukit Batikap, Central Kalimantan, Indonesia - IKE NURJUITA NAYASILANA; SUWARNO HADISUSANTO; HERY WIJAYANTO; SRI SUCI UTAMI ATMOKO; DIDIK PRASETYO; JAMARTIN SIHITE; CAREL P. VAN SCHAIK (Biodiversitas Journal of Biological Diversity, 2017)
Nayasilana IN, Hadisusanto S, Wijayanto H, Atmoko SSU, Prasetyo D, Sihite J, Van Schaik CP. 2017. Behavioral ecology of reintroduced Orangutans in the Bukit Batikap, Central Kalimantan, Indonesia. Biodiversitas 18: 875-886. Conversion habitat is the major threats to orangutan survival. More than 600 orangutans in rehabilitation center Nyaru Menteng BOSF, Central Kalimantan, waiting to be released to their nature habitat. The success of reintroduction is strongly dependent on the ecological component of the new habitat’s quality. Orangutans’ spatial behavior strongly related to fruit availability fluctuation, which will effects adaptation success. The goal of the study is to differentiate adaptation patterns of reintroduced orangutans (semi-wild and rehabilitant) base on habitat suitability. This study focused on 16 reintroduced orangutans (8 semi-wild and 8 rehabilitant) with a distribution of vegetation analysis overlaid with ranging for ecology effect. Day journey length and ranging of orangutans were collected for 18 months (2012- 2014) by means of focal animal sampling. Ranging data was analyzed using ArcMap GIS 9.3 Kernels program, the correlation between ranging and vegetation by Canonical Correspondence Analysis (CCA), diversity and biodiversity vegetation analysis which was then compared to wild orangutans (Sebangau and Tuanan Research Station). We found, 98% of Sorensen’s similarity in vegetation and similar diversity for Simpson’s, Shannon-Wiener and biodiversity indexes. Significantly high proportions of food patches consumed were fruit (p < 0.81) and rattan (p < 0.58). Our data also show the range of reintroduced orangutan vertical movements were between 0 m to >20 m, minimum home range for males was 619 ha and females 544 ha, with overlapping areas between orangutans 0.09%- 77.85%. Based on the correlation between ranging and food distribution, reintroduced orangutan distribution was found to be concentrated on food resources, with other factors indicating that they still felt comfortable around humans, and ranging was found to be similar compared to wild orangutans. In conclusion, an adaptation of reintroduced orangutans, both semi-wild and rehabilitated, in their new habitat was found to be similar.